Non-radioactive elements for prompt gamma enhancement in proton therapy. (July 2022) - Galanakou, Panagiota; Leventouri, Theodora; Muhammad, Wazir
Abstract: Regardless of advanced Prompt Gamma (PG) techniques developed to monitor proton range in-vivo, poor PG statistics downgrade the potential of their clinical implementation. We propose injection of the non-radioactive elements 19 F, 17 O, 127 I in a tumor area to enhance the PG production of 4.44 MeV and 6.13 MeV prompt gamma rays emitted after proton irradiation that have been correlated with the accurate monitoring of proton range during treatment. We simulated the interaction of 75 MeV, 100 MeV and 200 MeV incident proton beams in a co-centric cylindrical geometry phantom, where the outer cylinder was filled with 100% water and the inner cylinder (hypothetical tumor area) that is leveled with respect to the outer cylinder was filled with water containing 0.1%–20% weight fractions of each of the tested elements. We demonstrate that the proposed technique affects the PG statistics with results varying with the incident proton beam energy and mixture composition. PG enhancement in the energy range that facilitates proton range monitoring in-vivo is theoretically feasible after injecting an optimal amount of the non-radioactive element for a specific incident proton energy. Highlights: Stable elements in water alter prompt γ rays production after proton irradiation. 19 F, 17 O, and 127 I as potential prompt γ rays enhancers in proton therapy. Prompt γ rays enhancement depends on proton energy and irradiated composition. Improving prompt γ rays statistics to facilitate proton range monitoring in-vivo.